2023
DOI: 10.3201/eid2903.220632
|View full text |Cite
|
Sign up to set email alerts
|

New Detection of Locally Acquired Japanese Encephalitis Virus Using Clinical Metagenomics, New South Wales, Australia

Abstract: In the context of an emerging Japanese encephalitis outbreak within Australia, we describe a novel locally acquired case in New South Wales. A man in his 70s had rapidly progressive, fatal meningoencephalitis, diagnosed as caused by Japanese encephalitis virus by RNA-based metagenomic next-generation sequencing performed on postmortem brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…Overall, the lesions in C57BL/6J and Irf7 -/- mouse brains are consistent with H&E detectable lesions in post-mortem human JEV infected brains (6, 45, 56–58). To provide additional potential insights into the nature of the cellular infiltrates (e.g.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Overall, the lesions in C57BL/6J and Irf7 -/- mouse brains are consistent with H&E detectable lesions in post-mortem human JEV infected brains (6, 45, 56–58). To provide additional potential insights into the nature of the cellular infiltrates (e.g.…”
Section: Resultssupporting
confidence: 75%
“…Overall, the lesions in C57BL/6J and IRF7 -/mouse brains are consistent with H&E detectable lesions in post-mortem human JEV infected brains 6,38,[49][50][51] .…”
Section: Jev Causes Severe Histological Lesions In C57bl/6j and Irf7 ...supporting
confidence: 62%
“…To overcome this problem, increasing efforts have been directed in recent years to identify the causes of encephalitis using metagenomic next-generation sequencing. 12 13 14 In particular, Wilson, et al 15 reported in a prospective study that an additional infectious aetiology could be identified in 22% (13/58) of 208 encephalitis patients that could not be detected by conventional methods. Therefore, the future introduction of such diagnostic methods can greatly contribute to the exploration of the causes of encephalitis in Korean children.…”
Section: Discussionmentioning
confidence: 99%
“…The RAPIDprep assay was designed specifically as a rapid response tool, and it has proven to be effective in novel disease investigations, including identifying the first cases of the emergent Japanese encephalitis virus during the 2021-22 outbreak in south-eastern Australia [44][45][46] and characterizing the first cases of COVID-19 in NSW [35]. The assay has also been used to investigate non-human diseases, and it was critical to the genome recovery of a novel Hendra virus variant detected initially from a fatal equine infection by pan-paramyxovirus RT-PCR [2].…”
Section: Discussionmentioning
confidence: 99%